Electron transfer and electronic conduction through an intervening medium. - Edwards, P; Gray, H; Lodge, M; Williams, R (2008)
A new vision for ET: Electron-transfer (ET) processes in biological and synthetic materials (such as proteins and semi-conductors, respectively) are of immense importance. A unified approach to describe these processes is useful in understanding, and controlling the various facets of electron transfer in condensed matter. The diagram shows a plot of the decay constant for the electron-tunneling process against the effective tunneling barrier in different materials. (Graph Presented) © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.